Organic Cation Transporter 3 (Slc22a3) Is Implicated in Salt-Intake Regulation - Vialou, Vincent (J Neurosci, 2004)
Organic cation transporters (OCTs) are carrier-type permeases known to participate in general detoxification functions in peripheral tissues. Previous in vitro studies have suggested that OCTs ensure Uptake(2), a low-affinity, corticosteroid-sensitive catecholamine removal system, which was characterized initially in sympathetically innervated tissues. Although the presence of both Uptake(2)-like transport and most OCT subtypes has also been demonstrated in the brain, the physiological role of this family of transporters in CNS remained totally unknown. In the present work, we show that the OCT3 transporter is found throughout the brain and highly expressed in regions regulating fluid exchange, including circumventricular organs such as area postrema and subfornical organ (SFO), and in other structures implicated in the sensing of changes in blood osmolarity and regulation of salt and water ingestion. OCT3/Slc22a3-deficient mice show an increase in the level of ingestion of hypertonic saline under thirst and salt appetite conditions, as well as alterations of the neural response in the SFO after sodium deprivation, as monitored by Fos immunoreactivity. This work demonstrates that the presence of OCT3 is critical for the balanced neural and behavioral responses to environmentally induced variations in osmolarity and provides for the first time physiological evidence of the importance of OCTs for CNS function.